Feasibility and surgical impact of Z0011 trial criteria in a single‐Institution practice. Issue 7 (7th June 2020) - Morigi, Consuelo; Peradze, Nickolas; Galimberti, Viviana; Leonardi, Maria Cristina; Radice, Davide; Santomauro, Giorgia Irene; Bagnardi, Vincenzo; Intra, Mattia; Firpo, Emma; Veronesi, Paolo
Abstract: The purpose of this study is the evaluation of clinical and surgical impact of the Z0011 trial criteria on the management of breast cancer (BC) patients undergoing breast conservative surgery (BCS) at the European Institute of Oncology (IEO). We studied 1386 patients who underwent BCS and sentinel lymph node biopsy (SLNB) from July 2016 to July 2018. Clinical evaluation, breast ultrasound, mammogram, and cyto/histological examination were performed for all patients at the time of diagnosis. Frozen sections of the sentinel lymph node (SLN) were not performed for any patient. Patients who underwent neo‐adjuvant therapy were excluded. To evaluate the results before and after the introduction of Z0011 criteria, a group of 1425 patients with the same characteristics who underwent BCS and SLNB from July 2013 to July 2015 were analyzed. We studied the characteristics of the patients by nodal status, and we observed that T stage, tumor grade, and lymphovascular invasion were statistically related with the highest rate of positive SLN. Of the 1386 patients who underwent surgery after the introduction of the Z011 trial, 1156 patients (83.4%) had negative SLN, 230 patients (16.6%) had positive SLN. Subsequent axillary lymph node dissection (ALND) was performed in only 7 cases (3.0%). Of the 1425 patients operated before the introduction of the Z0011 trial, 216 patients had subsequent ALND (15%). The reduction in the number of ALND performed after the introduction of Z0011 is statistically significant, and this could result in a remarkable reduction of the comorbidities of our patients.